Northern Mindanao Medical Center Nurses and Precautionary Measures to Prevent Transmission of Hepatitis B - Carpo, Jocelyn (JPAIR Multidisciplinary Research, 2008)
The study determines the practice of taking precautionary measures by fifty NMMC staff nurses to prevent transmission of Hepatitis B. In relation to this, the study also tries to determine the clinical experience and the seminars on prevention of transmission of Hepatitis B attended by same nurses. For this research, the research team utilized a descriptive research design, purposive sampling was used, and questionnaire was used based on the theory of Nightingale on Environment, and the other on Hepatitis B Management of the Department of Health. Study results include clinical experience of between 1 - 5 years and attendance of 1 - 5 seminars on Hepatitis B Prevention. Practice of precautionary measures specifically in the administration of medication through injection is done 'sometimes' in terms of recapping the needle after injecting, 'most of the time' dispose syringes and needles and 'always' in terms of maintaining sterility in Immunization. However the same nursing staffs in NMMC 'always' practice precautionary measures especially in the disposal of waste and in handling patients with Hepatitis B in the ward sections. The research team recommended for the government to implement and promote massive immunization program so that Hepatitis B infection can be fully prevented. The team also urged the city government to conduct periodic check and monitoring of the implementation of precautionary measures in both private and government hospitals operating in Cagayan de Oro City.
Keywords: Precautionary Measures; Prevent Transmission of Hepatitis B